2019
DOI: 10.3389/fpls.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytonuclear Combinations Modify Arabidopsis thaliana Seed Physiology and Vigor

Abstract: Dormancy and germination vigor are complex traits of primary importance for adaptation and agriculture. Intraspecific variation in cytoplasmic genomes and cytonuclear interactions were previously reported to affect germination in Arabidopsis using novel cytonuclear combinations that disrupt co-adaptation between natural variants of nuclear and cytoplasmic genomes. However, specific aspects of dormancy and germination vigor were not thoroughly explored, nor the parental contributions to the genetic effects. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(76 reference statements)
0
10
0
1
Order By: Relevance
“…A significant effect of the cytoplasm genotype on seed germination efficiency was identified, suggesting a role of the selection on the plasmotype geographical distribution and its role in A. thaliana populations adaptation [36]. Another study conducted on the same cytolines concluded that cytonuclear interactions and coevolution had an impact on adaptive traits linked to seed vigor [78]. For example, the creation of novel CN combinations in cytolines, leading to the disruption of CN coadaptation, had a deleterious effect on adaptive dormancy and germination, consistent with a contribution of CN co-adaptation and cytoplasmic variation on complex traits involved in plant adaptation [78].…”
Section: Cytonuclear Coevolution and Environmentmentioning
confidence: 94%
See 1 more Smart Citation
“…A significant effect of the cytoplasm genotype on seed germination efficiency was identified, suggesting a role of the selection on the plasmotype geographical distribution and its role in A. thaliana populations adaptation [36]. Another study conducted on the same cytolines concluded that cytonuclear interactions and coevolution had an impact on adaptive traits linked to seed vigor [78]. For example, the creation of novel CN combinations in cytolines, leading to the disruption of CN coadaptation, had a deleterious effect on adaptive dormancy and germination, consistent with a contribution of CN co-adaptation and cytoplasmic variation on complex traits involved in plant adaptation [78].…”
Section: Cytonuclear Coevolution and Environmentmentioning
confidence: 94%
“…Another study conducted on the same cytolines concluded that cytonuclear interactions and coevolution had an impact on adaptive traits linked to seed vigor [78]. For example, the creation of novel CN combinations in cytolines, leading to the disruption of CN coadaptation, had a deleterious effect on adaptive dormancy and germination, consistent with a contribution of CN co-adaptation and cytoplasmic variation on complex traits involved in plant adaptation [78].…”
Section: Cytonuclear Coevolution and Environmentmentioning
confidence: 95%
“…The FDR was <0.01 corresponding to P values <0.003 for Fg proteins and to P values <0.002, <0.0018, and < 0.0006 for wheat proteins in the T, D, and T × D effects, respectively. Within all significant order 2 interactions, we computed a contrast test procedure to identify significant T × D interactions (Boussardon et al, 2018).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…When the number of observations is two times greater than the number of parameters of the model, we advise to include interaction terms between the biological factors. Such terms in the gene expression definition might reveal meaningful interactions such as genotype-environment interaction and answer in a direct way to some biological questions [39][40][41]. The (3) GLM_Contrasts function automatically writes a list of contrasts based on the model specified by the user.…”
Section: Differential Expression Analysismentioning
confidence: 99%